THU0471 Tocilizumab in Refractory Adult-Onset Still's Disease: Multicenter Study of 27 Patients. (23rd January 2014) - Ortiz-Sanjuán, F.; Blanco, R.; Narváez, F.; Rubio-Romero, E.; Castañeda, S.; Hernández, M.; Sifuentes-Giraldo, W.; Ros Vilamajó, I.; Mas, A.; Gallego Flores, A.; Manrique-Arija, S.; Gómez Arango, C.; et al.
Abstract : Background: Adult-onset Still's disease (AOSD) is often refractory to standard immunosuppressive therapy. Tocilizumab (TCZ) has shown efficacy in isolated cases or in small series. Objectives: We assess the efficacy of TCZ in AOSD. Methods: Multicenter study of 27 patients with AOSD of 18 hospitals diagnosed according to Yamagouchi's criteria (J Rheumatol 1992;19:424). TCZ was used due to lack of good response to standard therapy or to other biologic agents. Results: The 27 patients (20 women/ 7 men), had a mean age of 37.2±15.9 (range 16-71) and an average duration of AOSD of 5.9±4.6 years (range 0.1-17) to onset of TCZ. Prior to the onset of TCZ and besides corticosteroids, patients had recived the following drugs: Metotrexate (26 patients), Anakinra (12), Etanercept (6), Adalimumab (5) and Infliximab (3). TCZ standard dose was 8 mg/k/iv/4 weeks. At TCZ onset, the most frequent clinical manifestations were joint (27 cases), cutaneous (14) and fever (18), along with analytical abnomalities, increase of ESR or CRP (20 cases), anemia (11) or leukocytosis (15). Clinical and analytical improvement was observed soon, 1 st month after the onset of TCZ therapy (TABLE). After a mean follow-up of 20.8±12 months, cutaneous manifestations disappeared in 13 of 14 patients (92, 9%), fever in 17 of 18 (94.4%) and joint manifestation in 22 of 27 (81, 5%). Improvement of analytical abnormalities was observed in most cases with normalization of the blood cell count in 9 of 15 (60%) patients, anemia in 11 of 11 (100%), ESR in 15 of 19 (78.9 % ), CRP in 17 of 20 (85%), hepatic enzymes (AST/ALT) in 3 of 4 (50 %) and ferritin seric levels in 11 of 13 (84, 6%). The median [IQR] dose of steroids was reduced from 15 [8.8-25] to 5 [1.3-7.5]. Conclusions: In refractory AOSD, TCZ yields early and maintained clinical-analytical response, even in refractory cases to other biological agents. Although TCZ showed global efficacy, joint are more refractory than other systemic manifestations. Disclosure of Interest: None Declared